Chinese parents' caregiving ability for children with haematological malignancies: A latent class analysis. Issue 4 (18th April 2022) - Wang, Jingting; Bi, Xuanyi; Wang, Jichuan; Gu, Ying; Zheng, Xianlan; Wang, Yingwen; Wu, Huifang; Yang, Qi; Ma, Linyu; Liu, Fang; Yuan, Changrong
Abstract: Aim: The aim of this study was to identify unobserved subgroups of Chinese parents' caregiving ability for children with haematological malignancies and examine the associations of the latent class membership with individual characteristics. Design: A multicentre cross‐sectional survey study was conducted. Methods: A total of 392 parents of children with haematological malignancies in China were surveyed with the Hematologic Malignancies' Family Caregiver Skills Scale and a study‐specific demographic information questionnaire. Latent class analysis (LCA) and multinomial logistic regression model were applied in data analysis. Results: LCA results suggested that there existed three distinct a priori unknown classes of parents of children with haematological malignancies in regard to caregiving ability: Class 1—"high caregiving ability" class ( n  = 131, 33.4%), Class 2—"medium caregiving ability" class ( n  = 170, 43.4%) and Class 3—"low caregiving ability" class ( n  = 91, 23.2%). Socio‐demographics and clinical characteristics had significant associations with the latent class membership.